2020
DOI: 10.1097/fjc.0000000000000836
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Considerations in Treating Patients With Coronavirus Disease 2019 (COVID-19)

Abstract: A novel betacoronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread rapidly across the globe since December 2019. Coronavirus disease 2019 (COVID-19) has a significantly higher mortality rate than seasonal influenza and has disproportionately affected older adults, especially those with cardiovascular disease and related risk factors. Adverse cardiovascular sequelae, such as myocarditis, acute myocardial infarction, and heart failure, have been reported in patients with COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 61 publications
0
69
0
13
Order By: Relevance
“…Studies have shown that tocilizumab, an IL-6 receptor antibody, could reverse CRS in the setting of chimeric antigen receptor T-cell therapy for cancer [36]. Because of the greatly elevated serum levels of IL-6 in patients with COVID-19 [3], its off-label used in the early stage of the diseases suggests a favorable impact on the course of COVID-19 [37]. Moreover, in 2 small retrospective studies of COVID-19 patients in China suffering from severe lung injury it was observed that the use of this agent could provide significant clinical improvement without important side effects [38, 39].…”
Section: Cytokine-targeting Therapiesmentioning
confidence: 99%
“…Studies have shown that tocilizumab, an IL-6 receptor antibody, could reverse CRS in the setting of chimeric antigen receptor T-cell therapy for cancer [36]. Because of the greatly elevated serum levels of IL-6 in patients with COVID-19 [3], its off-label used in the early stage of the diseases suggests a favorable impact on the course of COVID-19 [37]. Moreover, in 2 small retrospective studies of COVID-19 patients in China suffering from severe lung injury it was observed that the use of this agent could provide significant clinical improvement without important side effects [38, 39].…”
Section: Cytokine-targeting Therapiesmentioning
confidence: 99%
“…8), several novel therapeutic approaches have been proposed, encompassing antivirals, antimalarials, and immunomodulators that have shown activity against SARS-CoV-2. 35,36 In particular, hydroxychloroquine, remdesivir, interferon β-1b, lopinavir-ritonavir, ribavirin, favipiravir, arbidol, tocilizumab, and bevacizumab have been investigated. 35 Mostly, however, these therapies have been evaluated in single cases or small-scale studies.…”
Section: Novel Therapeutic Approaches In Covid-19mentioning
confidence: 99%
“…Based on their experimental properties, chloroquine (CQ) and especially its analog hydroxychloroquine (HCQ) have been suggested [5], often associated with the macrolide antibiotic azithromycin (AZI) for alleged synergistic properties [6]. The anti-HIV protease inhibitor lopinavir, with ritonavir as a booster (LOPI), has also been used in this perspective.…”
Section: Introductionmentioning
confidence: 99%